The Market Impacts of Pharmaceutical Product Patents in Developing Countries: Evidence from India - Duggan, Mark; Garthwaite, Craig; Goyal, Aparajita (American Economic Review, 2016)
In 2005, as the result of a World Trade Organization mandate, India implemented a patent reform for pharmaceuticals that was intended to comply with the 1995 Trade-Related Aspects of Intellectual Property Rights (TRIPS). Exploiting variation in the timing of patent decisions, we estimate that a molecule receiving a patent experienced an average price increase of just 3–6 percent, with larger increases for more recently developed molecules and for those produced by just one firm when the patent system began. Our results also show little impact on quantities sold or on the number of pharmaceutical firms operating in the market. (JEL K33, L11, L13, L65, O14, O34, O38)